ESOTERICISM AND POLITICS: THEOSOPHY - Stašulāne, Anita (Via Latgalica, 2009)
Interference of esotericism and politics became apparent especially in the 19th century when the early socialists expected the coming of the Age of Spirit, and narratives about secret wisdom being kept in mysterious sacred places became all the more popular. Thus, the idea of the Age of Enlightenment underwent transformation: the world will be saved not by ordinary knowledge but by some special secret wisdom. In this context, Helena Blavatsky (1831–1891) developed the doctrine of Theosophy the ideas of which were overtaken by the next-generation theosophists including also the Russian painter Nicholas Roerich (1874–1947) and his spouse Helena Roerich (1879–1955) who developed a new form of Theosophy. The aim of this article is to analyse the interference between Theosophy and politics paying special attention to its historical roots, which, in the context of Roerich groups, are to be sought in the political activities of Nicholas Roerich, the founder of the movement. The following materials have been used in the analysis: first, writings of the founders of Agni Yoga or Teaching of Living Ethics; second, the latest studies in the history of Theosophy made in the available archives after the collapse of the soviet regime; third, materials obtained from the interviews of a field research (2006–2008). The author has made use of an interdisciplinary approach combining anthropological methods with the method of systematic analysis. The historical roots of the political activity of contemporary theosophists stretch into the political aspirations of Nicholas Roerich, the founder of Agni Yoga or Teaching of Living Ethics. Opening of the USSR secret archives and publication of several formerly inaccessible diaries and letters of theosophists offer an opportunity to study the “spiritual geopolitics” of the Roerichs. Setting off to his Central Asian expeditions (1925–1928; 1934–1935), Nicholas Roerich strived to implement the Great Plan, i.e. to found a New State that would stretch from Tibet to South Siberia comprising the territories governed by China, Mongolia, Tibet and the USSR. The new state was conceived as the kingdom of Shambhala on the earth, and in order to form this state, Nicholas Roerich aspired to acquire the support of various political systems. During the Tzarist Empire, the political world outlook of Nicholas Roerich was markedly monarchic. After the Bolshevik coup in Russia, the artist accepted the offer to work under the wing of the new power, but after his emigration to the West Roerich published extremely sharp articles against the Bolsheviks. In 1922, the Roerichs started to support Lenin considering him the messenger of Shambhala. Roerich’s efforts to acquire Bolshevik support culminated in 1926 when the Roerichs arrived in Moscow bringing a message by Mahatmas to the soviet government, a small case with earth for the Lenin Mausoleum from Burhan-Bulat and paintings in which Buddha Maitreya bore strong resemblance to Lenin. The plan of founding the Union of Eastern Republics, with Bolshevik support, failed, since about the year 1930 the soviet authorities changed their position concerning the politics of the Far East. Having ascertained that the Bolsheviks would not provide the anticipated support for the Great Plan, the Roerichs started to seek for contacts in the USA which provided funding for his second expedition (1934–1935). The Roerichs succeeded even in making correspondence (1934–1936) with President Roosevelt who paid much larger attention to Eastern states especially China than other presidents did. Their correspondence ceased when the Security Service of the USA grew suspicious about Roerich’s pro-Japanese disposition. Nicholas Roerich has sought for support to his political ambitions by all political regimes. In 1934, the Russian artist tried to ascertain whether German national socialists would support his efforts in Asia. It may seem that the plans of founding the Union of Oriental Republics have passed away along with Roerich; yet in 1991 his son Svyatoslav Roerich (1904–1993) pointed out once again that the Altai is a very important centre of the great future and Zvenigorod is still a great reality and a magnificent dream. Interference between esotericism and politics is observed also among Latvian theosophists: the soviet regime successfully made use of Roerich’s adherents propagating the communist ideology in the independent Republic of Latvia. In the 1920s and 1930s, the embassy of the USSR in Riga maintained close contacts with Roerich’s adherents in Latvia and made a strong pressure on the Latvian government not to ban the Roerich’s Museum Friend Society who actively propagated the success of soviet culture and economy. On 17 June 1940, the soviet army occupied the Republic of Latvia, and Haralds Lūkins, the son of the founder of the Roerich’s Museum Friend Society, was elected to the first government of the soviet Latvia. Nevertheless, involvement of theosophists in politics was unsuccessful, since after the official annexation of Latvia into the USSR, on 5 August 1940, all societies including the Roerich’s Museum Friend Society were closed. Since the members of the movement continued to meet regularly, in 1949, Haralds Lūkins was arrested as leader of an illegal organization. After the Second World War, theosophists were subjected to political repressions. Arrests of Roerich’s followers (1948–1951) badly impaired the movement. After rehabilitation in 1954, the repressed persons gradually returned from exile and kept on their illegal meetings in small groups. To regain their rights to act openly, Roerich’s followers started to praise Nicholas Roerich as a supporter of the soviet power. With the collapse of the soviet regime, Roerich’s followers in Latvia became legal in 1988 when the Latvian Roerich Society was restored which soon split up according to geopolitical orientation; therefore, presently in Latvia, there are the following organisations: Latvian Roerich Society, Latvian Department of the International Centre of the Roerichs, and Aivars Garda group or the Latvian National Front. A. Garda fused nationalistic ideas with Theosophy offering a special social reorganization – repatriation of the soviet-time immigrants and a social structure of Latvia that would be formed by at least 75% ethnic Latvians. Activity of A. Garda group, which is being criticized by other groups of theosophists, is a continuation of the interference between theosophical and political ideas practised by the Roerichs. Generally it is to be admitted that after the crush of the soviet regime, in theosophist groups, unclear political orientation between the rightists and leftists is observed, characterised by fairly radical ideas.